THE INFLUENCE OF CREATIVITY AND INNOVATION ON THE PERFORMANCE OF HANDMADE BATIK CRAFTSMEN IN KLAMPAR VILLAGE, PAMEKASAN REGENCY - Murtasima, Dewi; Samsuki, Samsuki (Universitas Islam Lamongan, 2025)
In this study, the focus is on exploring the extent to which imagination and innovation influence the performance of batik craftsmen in Klampar Village, Pamekasan Regency. The study was conducted using a quantitative approach with the application of multiple linear regression analysis. A total of 27 batik craftsmen were randomly selected to become respondents. The research findings revealed that both individually and together, creativity and innovation have a significant positive impact on the work performance of craftsmen. Specifically, creativity contributes 0.599, while innovation contributes more, namely 0.643. With a determination coefficient value of 55.9%, it can be seen that variations in craftsman performance can be substantially explained by these two variables. These findings emphasize the importance of developing creativity and innovation in increasing the productivity and competitiveness of batik craftsmen. This study recommends training, technological support, and strengthening marketing networks to support the sustainability of the Klampar Village batik industry.